Dismissing the Neoliberal Counter- reformation of State Capitalism - Merhar , Viljem; Žakelj, Žakelj; Mulej, Matjaž (Naše gospodarstvo/Our economy, 2014)
In neoliberal capitalism, global monopolies reign, not the market. They ruin competi- tion and limit the wages, employment, and purchasing capacity of 85% of humans. Thus, they ruin the market economy as a socio-economic system, applying the et- hics of independence and dependence, not the interdependence of Smith’s invisi- ble hand. The masses will not tolerate this much longer. It is urgent to link insights by Smith, Ricardo, Marx, Keynes, Galbraith, Felber, the European Union, etc., who see a way out of the current crisis of affluence and misery via a new socio-economic order comprising social responsibility, integral green economy, shared-value eco- nomy, and eco-socialism, thereby denying the state socialism of the 20th century.